2004
DOI: 10.1158/0008-5472.can-03-2664
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Expression of the Clusterin/Apolipoprotein J Gene in Human Cancer Cells Using Small Interfering RNA Induces Spontaneous Apoptosis, Reduced Growth Ability, and Cell Sensitization to Genotoxic and Oxidative Stress

Abstract: Clusterin/Apolipoprotein J (CLU) is a heterodimeric ubiquitously expressed secreted glycoprotein that is implicated in several physiological processes and is differentially expressed in many severe physiological disturbances, including tumor formation and in vivo cancer progression. Despite extensive efforts, clarification of CLU's biological role has been exceptionally difficult and its precise function remains elusive. Short RNA duplexes, referred to as small interfering RNAs (siRNAs), provide a new approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(198 citation statements)
references
References 57 publications
11
184
1
2
Order By: Relevance
“…A number of studies 1,5,13,16,17 have demonstrated that overexpression of the full-length CLU mRNA that would produce, depending on where the translation would start from and in this case, nCLU, acts as a prodeath signal, inhibiting cell growth and survival. However, other studies 2,6,8,10,[17][18][19] have shown that CLU expression may exert cytoprotective properties. We favour the recent proposal that tumour cell survival is connected with overexpression of sCLU and loss of nCLU.…”
Section: Clu Apoptosis and Cell Cycle Regulationmentioning
confidence: 95%
See 3 more Smart Citations
“…A number of studies 1,5,13,16,17 have demonstrated that overexpression of the full-length CLU mRNA that would produce, depending on where the translation would start from and in this case, nCLU, acts as a prodeath signal, inhibiting cell growth and survival. However, other studies 2,6,8,10,[17][18][19] have shown that CLU expression may exert cytoprotective properties. We favour the recent proposal that tumour cell survival is connected with overexpression of sCLU and loss of nCLU.…”
Section: Clu Apoptosis and Cell Cycle Regulationmentioning
confidence: 95%
“…2,4 These early apparently ambiguous functions appear to be attributed to the existence of two different but related CLU protein isoforms, a glycosylated as well as an apparently nonglycosylated form that are produced in the cell by alternative splicing. These two forms of the CLU protein can be immunologically distinguished.…”
Section: Two Clu Isoforms With Distinct Biologic Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, other apolipoproteins, such as apolipoprotein J/clusterin (CLU) and ApoE, may also be involved in the progression of human tumors. Trougakos etĀ al 30. showed that silencing of CLU suppressed cell growth and enhanced spontaneous apoptosis in osteosarcoma and PCa cells.…”
Section: Discussionmentioning
confidence: 99%